Surgical approaches in patients with empyema: Clinical evaluation - Muharrem, Cakmak; Evrim, Gul (Bayrakol Medical Publisher, 2020)
Aim: Surgical treatment procedures for empyema are tube thoracostomy, video-assisted thoracoscopic surgery (VATS), and thoracotomy. In this study, we aimed to share the characteristics and treatment outcomes of the patients with empyema treated with surgery. Materials and Methods: One hundred fifty-six patients were divided into 3 groups as patients who underwent tube thoracostomy (Group 1), VATS (Group 2), and thoracotomy (Group 3). Factors affecting the application of VATS-thoracotomy instead of tube thoracostomy and the application of thoracotomy instead of VATS were identified. The results were analyzed by the Fisher's exact test. P<0.05 was considered significant. Results: In Group 1 (n: 94), gram stain and culture results were positive in five (5%) patients, whereas negative results were found in 89 (95%). Loculation existed in five (5%) patients. In Group 2 (n: 6), in 2 patients (33%), gram stain and cultures were positive, while in 4 (67%) patients, they were negative. Loculation was present in 2 patients (33%). In Group 3 (n: 56), gram stain and cultures were positive in 19 (34%) patients, while they were negative in 37 patients (66%). Loculation existed in 53 patients (95%). The presence of positive gram stain and culture results, loculations, and purulent aspiration in thoracentesis were found to be more effective in preferring VATS-thoracotomy instead of tube thoracostomy. The presence of loculations only was found to be more effective in performing thoracotomy instead of VATS (p<0.05). Discussion: In cases where gram stain and culture are positive, and loculation and purulent aspiration exist, VATS and thoracotomy should be preferred.
Keywords: Empyema; Thoracoscopy; Thoracostomy; Thoracotomy